Contributions of Pedagogical Accompaniment to Advance the Quality of Teaching Practices in Rural Contexts - Beltrán-Veliz, Juan Carlos (2024)
Introduction. This original article presents findings from an investigation focusing on accompaniment to schools in rural contexts. Objective. This study aims to analyze the contributions of the pedagogical companion to the teaching practices of educators in rural schools in the Bío Bío region. Methodology. The study employs a qualitative approach and a collective case study design. Semi-structured interviews and documentary analysis were conducted with 19 General Basic Education teachers, aged between 22 and 65 years. Results. The main results reveal that the pedagogical companion plays a guiding role in collaboratively designing lesson plans. In addition, systematic and timely feedback, both oral and written, strengthens the higher-order thinking skills of the teachers being accompanied. Furthermore, pedagogical accompaniment fosters the innovation of teaching practices through peer collaboration, based on dialogue and reflection. Indeed, reflective practice is of vital importance in the training of teachers with critical thinking skills, thus benefiting professional development, which is reflected in the reformulation of teaching practice, oriented towards situated teaching and learning. The systematic pedagogical accompaniment develops the capacity for pedagogical leadership in the accompanied teachers. Conclusions. Pedagogical accompaniment is a key process in improving teaching practices and strengthening the professional performance of the teachers being tutored. This has a significant impact on student training and the generation of social transformations in rural education and in other educational contexts. In this sense, continuous self-improvement is recommended for teachers to meet the demands of contemporary society.